2012
DOI: 10.1111/j.1399-3054.2012.01658.x
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast‐targeted bacterial RecA proteins confer tolerance to chloroplast DNA damage by methyl viologen or UV‐C radiation in tobacco (Nicotiana tabacum) plants

Abstract: The nature and importance of the DNA repair system in the chloroplasts of higher plants under oxidative stress or UV radiation-induced genotoxicity was investigated via gain-of-functional approaches exploiting bacterial RecAs. For this purpose, transgenic tobacco (Nicotiana tabacum) plants and cell suspensions overexpressing Escherichia coli or Pseudomonas aeruginosa RecA fused to a chloroplast-targeting transit peptide were first produced. The transgenic tobacco plants maintained higher amounts of chloroplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Recombination also occurs between large inverted repeats (Kolodner and Tewari, 1979), and chloroplasts are transformed by targeted integration of foreign DNA (Boynton et al, 1988), collectively suggesting the existence of RecArelated active HR in chloroplasts. Recently, some T-DNA mutants of the cpRECA gene AtRECA1, one of three A. thaliana RECA genes, have been shown to exhibit leaf variegation (Rowan et al, 2010) or no visible phenotype (Jeon et al, 2013). The variegated cpRECA mutants also exhibit elevated levels of single-stranded DNA and reduced levels of cpDNA (Rowan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recombination also occurs between large inverted repeats (Kolodner and Tewari, 1979), and chloroplasts are transformed by targeted integration of foreign DNA (Boynton et al, 1988), collectively suggesting the existence of RecArelated active HR in chloroplasts. Recently, some T-DNA mutants of the cpRECA gene AtRECA1, one of three A. thaliana RECA genes, have been shown to exhibit leaf variegation (Rowan et al, 2010) or no visible phenotype (Jeon et al, 2013). The variegated cpRECA mutants also exhibit elevated levels of single-stranded DNA and reduced levels of cpDNA (Rowan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial-derived recombinase RecA (PHATRDRAFT_54013) is expressed in the nuclear genome but localizes to the chloroplast after translation, where it mediates homologous recombination. Previous studies have demonstrated that disrupting this gene in a variety of distantly related photosynthetic eukaryotes disrupts homologous recombination within the chloroplast (Cerutti et al, 1995;Jeon et al, 2013). This will be necessary to prevent homologous recombination between the endogenous and cloned genomes, which posed challenges during transformation of the Chlamydomonas chloroplast genome (O'Neill et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that cpRECA may suppress aberrant recombination between SDRs in cp and play a similar role in maintaining cp genome stability to that of mitochondrial RECA in mitochondrial genome stability (Odahara et al, 2009). After reproduction for several generations, Arabidopsis cpRECA mutants exhibited variegation in leaves and enhanced sensitivity to DSBand reactive oxygen species-inducing agents (Rowan et al, 2010;Jeon et al, 2013). In addition, compared with the wild type, mutants exhibit a reduction in cpDNA copy number, an increase in single-stranded cpDNA, and cpDNA structural alterations (Rowan et al, 2010).…”
mentioning
confidence: 99%